Spermidine Enhances Mitochondrial Bioenergetics in Young and Aged Human-Induced Pluripotent Stem Cell-Derived Neurons - Leonora Szabo; Imane Lejri; Amandine Grimm; Anne Eckert (Antioxidants)
The accumulation of damaged mitochondria has long been considered a hallmark of the aging process. Among various factors, age-related mitochondrial alterations comprise bioenergetic impairments and disturbances in reactive oxygen species (ROS) control, thereby negatively affecting mitochondrial performance and ultimately accelerating aging. Previous studies have revealed that polyamine spermidine appears to exert health-protective and lifespan-promoting effects. Notably, recent findings have also described a spermidine-induced improvement in age-associated mitochondrial dysfunction, but the beneficial effects of spermidine on aged mitochondria have not been entirely examined yet. Here, we show that spermidine positively regulates several parameters related to mitochondrial bioenergetics and mitochondrial redox homeostasis in young and aged human-induced pluripotent stem cell-derived neurons. We report that spermidine treatment increases adenosine triphosphate production and mitochondrial membrane potential, which is accompanied by an attenuation in mitochondrial ROS levels in both age groups. Furthermore, we demonstrate a spermidine-mediated amelioration in mitochondrial respiration in both young and aged neurons. Overall, our findings suggest that nutritional spermidine supplementation might represent an attractive therapeutic approach to enhance mitochondrial function, consequently decelerating aging.